Alleviating acid soil stress in cowpea with a local population of arbuscular mycorrhizal fungi - Kongpun A. (2014)
In Huai Teecha village in Northern Thailand, local cowpeas were grown on acidic low phosphorus soil without stress symptoms. Arbuscular mycorrhizal fungi from this system have been found to promote growth of many crops but there is no information about their benefit in cowpea. In a field experiment, three improved cowpea lines (ITD - 1131, Ubon Ratchathani and IT90K - 227 - 2) and a local line (Teecha 1) were grown in 3 farmer's fields on acid low P soils. Roots of the cowpea lines were all heavily colonized by the fungi and their leaf P was within the sufficient range. In a pot experiment, the cowpea line Ubon Ratchathani was grown in acidic and non acidic (pH 5 and 6.7, respectively) soil with three rates of phosphorus (50, 104 and 141 mg phosphorus pot-1) with and without arbuscular mycorrhizal fungi inoculation. Total dry weight of inoculated cowpea was not affected by soil acidity while it was depressed in un-inoculated plants. The fungi increased total dry weight at 50 and 104 mg phosphorus ha-1 but had no effect at 141 mg phosphorus pot-1. Therefore, the fungi had been shown to enhance P uptake by cowpea roots, which resulted in direct benefit to cowpea growth in acidic low P soil. © 2011 Academic Journals.